Pergeseran Ritual Robo-Robo: Studi tentang Relasi Personal, Komunitas, dan Tokoh Politik-Keagamaan di Ketapang Kalimantan Barat - Baha’udin; Syahbudi (LP2M Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This study examines the transformation of the Robo-Robo ritual in Ketapang, West Kalimantan, as a multi-actor contestation arena involving personal-spiritual, communal-cultural, and politico-religious dimensions. Employing a critical ethnographic approach, the research explores how this Safar month ritual has transformed from a simple community-based practice into a formalized public event. Findings reveal shifts from household to sub-district scale, from riverine to mosque settings, and institutional formalization, while traditional meanings as a medium for prayers of safety, disaster prevention, and social unity remain preserved. These shifts reflect complex negotiations between maintaining tradition and adapting to modernity, involving ritual practitioners, tradition bearers, and politico-religious elites. This research contributes to understanding the dynamics of local religious ritual transformation in contemporary Indonesian Islam, revealing how local rituals become symbolic battlegrounds while maintaining their function as markers of Malay-Islamic community identity.